STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SEBAGAI KUNCI PENINGKATAN KEPUASAN KONSUMEN PADA INDUSTRI HASIL HUTAN KALIMANTAN TIMUR - Nona, Risna; Wahyuningtyas, Irma; Rizki, Selvi Diliyanti; Badia, Bahdin Ahad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to prove and analyze the influence of Customer Relationship Management (CRM) as a key strategy on increasing Customer Satisfaction for forest products industry in East Kalimantan. This research employed a quantitative approach with a survey method, where primary data were collected by distributing questionnaires to 278 consumers selected using a simple random sampling technique. Data analysis was performed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) approach with SmartPLS software. The results show that Customer Relationship Management (CRM) has a positive and statistically significant effect on Customer Satisfaction, as evidenced by a path coefficient of 0.249 and a T-statistic of 3.973 (P-value < 0.05). The R-Square value of 0.062 indicates that CRM is able to explain 6.2% of the variance in Customer Satisfaction. This finding confirms that the implementation of CRM strategies, particularly through ease of service access and the maintenance of personal relationships, is a crucial factor that can enhance consumer satisfaction in the forest products industry sector.